Prevention of Surgical Site Infections: A Systematic Review of Cost Analyses in the Use of Prophylactic Antibiotics - Purba, Abdul K. R.; Setiawan, Didik; Bathoorn, Erik; Postma, Maarten J.; Dik, Jan-Willem H.; Friedrich, Alex W. (Frontiers in Pharmacology, 2018)
Introduction: The preoperative phase is an important period in which to prevent surgical site infections (SSIs). Prophylactic antibiotic use helps to reduce SSI rates, leading to reductions in hospitalization time and cost. In clinical practice, besides effectiveness and safety, the selection of prophylactic antibiotic agents should also consider the evidence with regard to costs and microbiological results. This review assessed the current research related to the use of antibiotics for SSI prophylaxis from an economic perspective and the underlying epidemiology of microbiological findings. Methods: A literature search was carried out through PubMed and Embase databases from 1 January 2006 to 31 August 2017. The relevant studies which reported the use of prophylactic antibiotics, SSI rates and costs were included for analysis. The causing pathogens for SSIs were categorized by sites of the surgery. The quality of reporting on each included study was assessed with the “Consensus on Health Economic Criteria” (CHEC). Results: We identified 20 eligible full-text studies that met our inclusion criteria were subsequently assessed, resulting in a reporting quality scored on the CHEC list averaging 13.03 (8-18.5). Of the included studies, 14 were trial-based studies, and the others were model-based studies. The SSI rates ranged from 0 to 71.1% with costs amounting to US$480-22,130. Twenty-four bacteria were identified as causative agents of SSIs. Gram negatives were the dominant causes of SSIs especially in general surgery, neurosurgery, cardiothoracic surgery and obstetric cesarean sections. Conclusions: Varying results were reported in the studies reviewed. Yet, information from both trial-based and model-based costing studies could be considered in the clinical implementation of proper and efficient use of prophylactic antibiotics to prevent SSIs and antimicrobial resistance. Nevertheless, the findings of economics and microbiology from the included studies have reported diverse results.